A high-throughput single cell-based antibody discovery approach against the full-length SARS-CoV-2 spike protein suggests a lack of neutralizing antibodies targeting the highly conserved S2 domain. Issue 3 (31st March 2022) - Chai, Mengya; Guo, Yajuan; Yang, Liu; Li, Jianhui; Liu, Shuo; Chen, Lei; Shen, Yuelei; Yang, Yi; Wang, Youchun; Xu, Lida; Yu, Changyuan
Abstract: Coronavirus disease 2019 pandemic continues globally with a growing number of infections, but there are currently no effective antibody drugs against the virus. In addition, 90% amino acid sequence identity between the S2 subunit of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and SARS-CoV S proteins attracts us to examine S2-targeted cross-neutralizing antibodies that are not yet well defined. We therefore immunized RenMab mice with the full-length S protein and constructed a high-throughput antibody discovery method based on single-cell sequencing technology to isolate SARS-CoV-2 S-targeted neutralizing antibodies and cross-neutralizing antibodies against the S2 region of SARS-CoV-2/SARS-CoV S. Diversity of antibody sequences in RenMab mice and consistency in B-cell immune responses between RenMab mice and humans enabled screening of fully human virus-neutralizing antibodies. From all the frequency >1 paired clonotypes obtained from single-cell V(D)J sequencing, 215 antibodies with binding affinities were identified and primarily bound S2. However, only two receptor-binding domain-targeted clonotypes had neutralizing activity against SARS-CoV-2. Moreover, 5' single-cell RNA sequencing indicated that these sorted splenic B cells are mainly plasmablasts, germinal center (GC)-dependent memory B-cells and GC B-cells. Among them, plasmablasts and GC-dependent memory B-cells were considered the most significant possibility of producing virus-specific antibodies. Altogether, using a high-throughput single cell-based antibody discovery approach, our study highlighted the challenges of developing S2-binding neutralizing antibodies against SARS-CoV-2 and provided a novel direction for the enrichment of antigen-specific B-cells.